2022
DOI: 10.1088/1741-2552/ac6828
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mental schema evolution on mental workload measurement: an EEG study with simulated quadrotor UAV operation

Abstract: Objective: Mental workload is the result of the interactions between the demands of an operation task and the skills, behavior and perception of the performer. Working under a high mental workload can significantly affect an operator’s ability to choose optimal decisions. However, the effect of mental schema, which reflects the level of expertise of an operator, on mental workload remains unclear. Here, we propose a theoretical framework for describing how the evolution of mental schema affects mental workload… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 69 publications
1
4
0
1
Order By: Relevance
“…These findings were similar to previous research on the patterns of band power changes due to stress when participants were asked to perform a time-limited examination task [53]. Similarly, Gu et al [54] suggested that the decrease in theta power is a symptom of increased mental effort in a state of increased task stress, which is consistent with previous studies [55]. Theta band might facilitate recurring cycles of integration across multiple inputs (environment, reward, memory) to inform controlled action choices [56], and therefore a decline in theta activity might suggest a decline in this integration capacity.…”
Section: Critical Frequency Bands For Emotion Recognitionsupporting
confidence: 90%
“…These findings were similar to previous research on the patterns of band power changes due to stress when participants were asked to perform a time-limited examination task [53]. Similarly, Gu et al [54] suggested that the decrease in theta power is a symptom of increased mental effort in a state of increased task stress, which is consistent with previous studies [55]. Theta band might facilitate recurring cycles of integration across multiple inputs (environment, reward, memory) to inform controlled action choices [56], and therefore a decline in theta activity might suggest a decline in this integration capacity.…”
Section: Critical Frequency Bands For Emotion Recognitionsupporting
confidence: 90%
“…The assessment of EEG correlates of force exertions should also consider the effects of perceptual and cognitive processes [94]. Moreover, we acknowledge that the reported EEG results could be partially affected by high individual differences among the participants and the limitations of power spectra density measures [95]. Future studies should include a much larger study of male and female populations to increase the power of the investigated relationships between the exerted forces, physical comfort, and their EEG signatures.…”
Section: Discussionmentioning
confidence: 98%
“…All participants gave written informed consent before participation and underwent 10-day UAV flight training. A more detailed description is provided in a previously published article [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…( a ) Simulated UAV operation tasks and experimental environment. ( b ) Schematic of the study procedure (adopted from Gu et al, 2022 [ 32 ]).…”
Section: Figurementioning
confidence: 99%